Capacidades estatais para a implementaç\~ao de programas de transferência de renda: Os casos de Brasil, Argentina e África do Sul - Renata Mirandola Bichir (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This research analyzes the principal conditions that allowed the development of national cash transfer programs in the social protection systems of Brazil, Argentina and South Africa. The main focuses are the political and institutional conditions for the emergence and development of these programs in the policy agenda, as well as the articulation of these and other social policies - such as social assistance, education, health and employment generation and income -, in order to understand problems of coordination and intersectoral coordination. The guiding questions are: What are the main institutional dimensions that organize cash transfer programs in Brazil, Argentina and South Africa? How distinct state capacities and political choices organize these arrangements?
Keywords: I38; F55; H75; 330; state capacity; cash transfer programs; social policies; Brazil; Argentina; South Africa